Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1101/2023.03.01.530562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Esm-1 mediates transcriptional polarization associated with diabetic kidney disease

Abstract: BackgroundEsm-1, endothelial cell-specific molecule-1, is a susceptibility gene for diabetic kidney disease (DKD) and is a cytokine- and glucose-regulated, secreted proteoglycan, that is notably expressed in kidney and attenuates inflammation and albuminuria.Esm1has restricted expression at the vascular tip during development but little is known about its expression pattern in mature tissues, and its precise effects in diabetes.MethodsWe utilized publicly available single-cell RNA sequencing data to explore th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
(113 reference statements)
0
0
0
Order By: Relevance
“…These results contrast with those of a study exploring the renal expression of endocan in mice, which identified endothelial cells as the quasi-exclusive source of this molecule. 6 In naïve mice, epithelial absolute expression is lower than the endothelial one, though a down-regulation of the endothelial fraction of Esm1 expression seems to be observed in ALI until day 5. These variations show some dissimilarities with the apparent increase observed in endocan blood levels from day 1 to 5 following LPS administration, implying a possible influence of extra-pulmonary sources of expression of endocan.…”
Section: F I G U R Ementioning
confidence: 92%
“…These results contrast with those of a study exploring the renal expression of endocan in mice, which identified endothelial cells as the quasi-exclusive source of this molecule. 6 In naïve mice, epithelial absolute expression is lower than the endothelial one, though a down-regulation of the endothelial fraction of Esm1 expression seems to be observed in ALI until day 5. These variations show some dissimilarities with the apparent increase observed in endocan blood levels from day 1 to 5 following LPS administration, implying a possible influence of extra-pulmonary sources of expression of endocan.…”
Section: F I G U R Ementioning
confidence: 92%